GROWTH RATE OF (Anadara granosa) SPAT ON THE NATURAL HABITAT WITH DIFFERENT DENSITY IN PANIPAHAN BEACH ROKAN HILIR RECIDENT RIAU PROVINCE - Suardi '; Syafruddin Nasution; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this study was to determine the growth rate of A. granosa with different stocking density. This study was conducted from November 2015 to January 2016. Animals test measuring between 0.8-1.0 cm. The method used in this study is experimental method with completely randomized design (CRD), one factor with 4 treatments. To minimize errors, each treatment using 3 replicates. Treatment A (50 individuals), B (75 individuals), C (100 individuals), D (125 individuals). The variables measured were the growth rate and survival rate. The results showed that the stocking density of 50 individuals generate growth in the value of the highest average or better than stocking density 75 individuals and 100 individuals, while stocking density of 125 individuals was the lowest growth. The highest level of survival was found on a stocking density of 50 individuals with an average value of 92.7 ± 3.055%, while the lowest survival was on stocking density 125 individuals with an average value of 83.5 ± 1.222%.Keywords: Anadara granosa, stocking density, growth rate, Panipahan beach